Generation and characterization of avian-derived anti-human CD19 single chain fragment antibodies. Issue 4 (2nd October 2019) - Tsai, Keng-Chang; Chiang, Chen-Wei; Lo, Yan-Ni; Chang, Fu-Ling; Lin, Tsai-Yu; Chang, Chang-Yu; Chen, Wang-Chuan; Lee, Yu-Ching
Abstract: The human cluster of differentiation 19 (CD19) is highly expressed in most leukemia, rendering is a promising therapeutic target. In this study, we generated anti-CD19 single-chain variable fragments (scFv) from immunized chickens by phage display technology. After constructing a scFv antibody library with 2.5 × 10 8 compositional diversity for panning, one representative scFv clone S2 which can specifically recognize to the CD19 protein was isolated and characterized. The binding reactivity of the scFv S2 to the endogenous CD19 protein of the ARH-77 leukemia cancer cell was verified through flow cytometry and the binding affinity of scFv S2 is 6.9 × 10 −8 M determined by the surface plasmon resonance system. Compared with the chicken germline, hyper mutation in the complementarity-determining regions (CDRs) suggested that scFv S2 could be generated through an antigen-driven humoral response. By molecular modeling, the possible CDR configurations of scFv S2 were constructed rationally. Furthermore, the characteristics of chicken antibodies of a protein database were investigated. The findings in this study contribute to antibody development and engineering because they reveal the geometric structures and properties of the CDRs in chicken antibodies.